The making of Port of Spain: The history of Port of Spain. volume 1, 1757-1939. - Anthony, Michael. (Paria Publishing Company Limited, 2011)
The early settlements days of Port of Spain from 1757 to the Second World War. The Spanish invasion of Trinidad and Tobago, the memories of old time Carnival, the great fires of the city, the Butler riots, the introduction of the telephone, etc.
Keywords: History - Port of Spain, Historic buildings - Port of Spain, of Spain.